The development and validation of an instrument to assess the religious knowledge of students and teachers specializing in religious education in the four Canossian schools of the Philippines - Peralta, Josefina, FdCC. (Animo Repository, 1995)
This research develops and validates an instrument that assesses the religious knowledge of students and teachers specializing in religious education among four Canossian schools in the Philippines. The content of the assessment instruments was gleaned from the religious knowledge summarized in the three new documents of the Church -- the Catholic Catechism (CCC), Second Plenary Council of the Philippines (PCP II), and the Catholic Faith Catechism (CFC).The research used the descriptive developmental research method. The steps included (1) specifying the purpose of the test, (2) translating the purpose of the test, (3) constructing the items, (4) filed testing and item analysis, (5) validity and reliability study, and (6) assembling the final form of the test (a revision of the prototype instrument) called Assessment of the Religious Knowledge (ARK).The respondents for this study consisted of 20 junior and 20 senior college students enrolled during the first semester of SY 1994-1995 in Canossa College, San Pablo, Laguna, and 51 Religion teachers of four Canossian Schools. The developed and validated instrument was called Assessment of the Religious Knowledge (ARK). Item analysis revealed the discriminative power of the items across years of study and teaching experience. Teachers scored higher in almost all areas. All components showed moderate to moderately high significant reliability coefficients (p.01). Such moderate level excluded the area on Christian Living which yielded a high significant reliability index. The analysis of variance detected significant differences between the mean of the three groups. This gave credibility to the instrument's power to draw varied responses from the respondents and to discriminate the high scores from th low scores. Christian life, sacraments and religious knowledge were consistently grouped to have moderate to high intercorrelation coefficients. Thirty-three percent of the variance in the difference of scores on the test was due to the difference in the study levels or years of teaching experience. This indicated the power of the ARK to assess religious knowledge.